2013
DOI: 10.1371/journal.pone.0070518
|View full text |Cite
|
Sign up to set email alerts
|

Mcm10 Self-Association Is Mediated by an N-Terminal Coiled-Coil Domain

Abstract: Minichromosome maintenance protein 10 (Mcm10) is an essential eukaryotic DNA-binding replication factor thought to serve as a scaffold to coordinate enzymatic activities within the replisome. Mcm10 appears to function as an oligomer rather than in its monomeric form (or rather than as a monomer). However, various orthologs have been found to contain 1, 2, 3, 4, or 6 subunits and thus, this issue has remained controversial. Here, we show that self-association of Xenopus laevis Mcm10 is mediated by a conserved c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 78 publications
3
33
0
Order By: Relevance
“…Semi-quantitative chromatin binding studies are consistent with recent findings that revealed that the conserved CC domain in the NTD enables XMcm10 to dimer- and trimerize in a highly dynamic fashion [5, 8, 15]. Removal of the corresponding motif in ScMcm10 leads to severe hydroxyurea (HU) sensitivity when checkpoint function is compromised [8](Alver and Bielinsky, unpublished). The NTD has also been implicated in oligomerization of human (Hs) Mcm10 [16].…”
Section: Structure and Function Of Mcm10supporting
confidence: 82%
See 3 more Smart Citations
“…Semi-quantitative chromatin binding studies are consistent with recent findings that revealed that the conserved CC domain in the NTD enables XMcm10 to dimer- and trimerize in a highly dynamic fashion [5, 8, 15]. Removal of the corresponding motif in ScMcm10 leads to severe hydroxyurea (HU) sensitivity when checkpoint function is compromised [8](Alver and Bielinsky, unpublished). The NTD has also been implicated in oligomerization of human (Hs) Mcm10 [16].…”
Section: Structure and Function Of Mcm10supporting
confidence: 82%
“…Several reports suggest that Mcm10 has a strong preference for ss over ds DNA [10, 12, 13], providing a rationale of how Mcm10 might contribute to the activation of the Cdc45:Mcm2-7:GINS (CMG) helicase [14]. Semi-quantitative chromatin binding studies are consistent with recent findings that revealed that the conserved CC domain in the NTD enables XMcm10 to dimer- and trimerize in a highly dynamic fashion [5, 8, 15]. Removal of the corresponding motif in ScMcm10 leads to severe hydroxyurea (HU) sensitivity when checkpoint function is compromised [8](Alver and Bielinsky, unpublished).…”
Section: Structure and Function Of Mcm10supporting
confidence: 78%
See 2 more Smart Citations
“…Toward this end, we constructed N-terminal truncation mutants of Mcm10 that left the PIP box intact, but deleted the first 50, 100 or 150 amino acids (Figure 2A). This region of Mcm10 lies outside the conserved OB-fold/Zn-finger domain and is not predicted to have any significant secondary structure (17), except for a coiled-coil region at the very N-terminus (21). All fusion proteins were expressed (Figure 2B and Supplementary Figure S1) and we then assessed binding to Mec3 via two-hybrid analyses (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%